(untitled) (LEARNing Landscapes, 2009)
The context for this paper is a teacher education program for adult literacy practitioners at Queen’s University Belfast in Northern Ireland.This paper describes and reflects on the use of arts-based approaches to enhance these practitioners’ conceptualizations of literacy, presenting their arts-based responses and their evaluations of the methods. The discussion raises questions about the inclusion of visual literacy in adult literacy teacher education programs.